Історичні витоки фермерства на Волині - Шабала, Б. (Краєзнавство, 2019)
У статті з'ясовуються історичні витоки традицій індивідуального селянського господарювання у
добу пізнього середньовіччя, аналізуються ознаки формування фермерських начал у сільському господарстві України і Волині у період утвердженням капіталістичних ринкових відносин в середині ХІХ – на
початку ХХ ст., порушується проблема функціонування господарств фермерського типу у 20–30-х рр.
ХХ ст. на території сучасної Волинської області, визначаються головні чинники формування фермерського укладу в аграрному секторі. The historical origins of the traditions of individual peasant farming in the late Middle Ages are revealed,
characterized by the consolidation of individual and family land usage and the formation of traditions of rational
attitude to land resources, affirmation in the practice of managing such features as economic acumen
and entrepreneurship. The signs of the formation of agricultural principles in agriculture of Ukraine and Volyn
during the period of the establishment of capitalist market relations in the middle of the nineteenth – early
twentieth centuries are analyzed, in particular, such as individual farming on their own or leased land and production
of commodity agricultural products. Violated the problem of farm functioning in the 20’s and 30’s of
the twentieth century on the territory of the modern Volyn Oblast, in terms of the implementation of agrarian
reform of the Second Poland Partition Government that included large land ownership restrictions; formation
of the land market; the formation of different types and sizes of farms that would be based on private land ownership;
land-use improvement through land consolidation – the unification of disparate land owned by one
owner into one allotment.